THE EFFECT OF ADDITION OF TURMERIC FLOUR (Curcuma longa Linn) INFEED ON THE PERFORMANCE OF THE GROWTH AND IMMUNE SYSTEM OF FISH (Oreochromis niloticus) - Sari Damayanti; Sadikin Amir; Fariq Azhar (Journal of Fish Health, 2022)
This study aims to determine tilapia's growth and immune system (Oreochromis niloticus) through feeding with added turmeric flour. This study used a completely randomized design with five treatments, namely K- (feed without adding turmeric flour and injected with physiological solution), K+ (feed without adding turmeric flour and injected with A. hydrophila bacteria), P1 (addition of turmeric flour 1 % / kg of feed + bacterial infection of A. hydrophilla), P2 (Addition of 2% turmeric flour/kg of feed + bacterial infection of A. hydrophilla), and P3 (Addition of 3% turmeric flour/kg of feed + bacterial infection of A. hydrophilla) each treatment had three replicates for a total of 15 trials. The results showed that there was a significant effect (p > 0.05) on growth but no significant effect (p < 0.05) on the survival of tilapia, so further tests were carried out to determine the best treatment in producing tilapia growth, it is known that P2 (Addition of 2% turmeric flour/kg of feed + bacterial infection of A. hydrophilla) is the best treatment in this study.